Participation restriction in childhood phenotype of myotonic dystrophy type 1: a systematic retrospective chart review. (27th September 2016) - Gagnon, Cynthia; Kierkegaard, Marie; Blackburn, Catherine; Chrestian, Nicolas; Lavoie, Mélissa; Bouchard, Marie‐Frédéric; Mathieu, Jean
Abstract : Aim: Myotonic dystrophy type 1 (DM1), a neuromuscular disorder, is divided into four clinical phenotypes: congenital; childhood; adult‐onset, and late‐onset. Publications about the childhood phenotype, especially the long‐term outcome, are scarce. The aims of this study were to assess and describe participation outcomes in adults with the childhood phenotype. Method: A retrospective chart methodology. Data were extracted from health records for 63 adults with childhood DM1 (32 males, 31 females; mean age 34y, standard deviation [SD] 11y 6mo; range 18–54y) who had attended the Saguenay Neuromuscular Clinic, Canada. Results: Thirty‐four adults (54%) lived with their parents or in foster homes, and most patients needed services or help to live independently. A significant proportion (22%) were isolated in regard to friendship. Very few adults had children, although 33% lived with a spouse. The majority of patients (86%) relied on social security and only one person was currently working. Financial responsibilities were often an issue and 13 (21%) were under legal guardianship. Interpretation: This study showed that patients with the childhood phenotype present a guarded prognosis regarding long‐term social participation. These participation restrictions could be related to behavioural, cognitive, and social stigma problems in childhood. This study illustrates the absolute necessity to pursue an interdisciplinary follow‐up of these patients when they are reaching adulthood. What this paper adds: Myotonic dystrophy type 1 (DM1) childhood phenotype presents a guarded prognosis regarding long‐term participation. Ninety‐five per cent had a history of educational difficulties. More than 50% lived with their parents or in foster homes during adulthood.